Siriah Gadang Cultural Values in Galombang Dance in Pariangan, West Sumatra - Asriati, Afifah; Shafii, AS Hardy; Yuliasma, Yuliasma; Putra, Irdhan Epria Darma; Desfiarni, Desfiarni (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
This article aims to expose the revitalization of Siriah Gadang cultural values in Galombang dance performed in Guguak village, Pariangan, Tanah Datar Regency, West Sumatra. Siriah Gadang is almost extinct because it is very rarely used. It is a cultural object with the same function as Carano, which is currently used for Galombang dance performances. To achieve this goal, qualitative research was used through observation, documentation, in-depth interviews, and Focus Group Discussion (FGD) techniques. The data obtained were analyzed using the Miles and Haberman model. It was found that the cultural values in Siriah Gadang are customary values, ethical values, social values, religious values, and leadership values reflected in the philosophy of the Minangkabau people “adaik basandi syarak, syarak basandi Kitabullah.”